The successful use of a bespoke OssDsign cranial plate to reconstruct an occipital defect following excision of a recurrent epithelioid sarcoma. (June 2020) - Bloom, Oliver; Goddard, Naveen; Yannoulias, Basil; Eccles, Simon
Abstract: A cranioplasty has a number of known associated complications including infection for non-biological implants and bone flap resorption where autologous grafts are used. In recent years, bioactive ceramic cranial implants have been developed as a new reconstructive option. The OssDsign cranial plate (OssDsign AB, Uppsala, Sweden) was first introduced in 2010 and consists of an interconnected mosaic of hydroxyapatite tiles mounted onto a 3D-printed titanium mesh. Each tile is composed of a monetite, beta-calcium pyrophosphate, beta-tricalcium phosphate and brushite compound designed to mimic the process of coupled bone formation once implanted. This case presents a patient's journey from diagnosis of an epithelioid sarcoma over the posterior scalp and its management in the following 7 years. Initial excision of the lesion was reconstructed with a tissue expander and local rotational flap. Recurrence of the disease 3 years later was treated with a course of radical radiotherapy. Persistent osteomyelitis over the next 3 years resulted in chronic ulceration and exposed bone in the treated area. As the first part of a 3-stage treatment plan, two separate tissue expanders became infected. The multidisciplinary team therefore chose to use a bespoke OssDsign cranial plate combined with a deep inferior epigastric perforator (DIEP) free flap to provide a definitive single operative solution. The advantages over other reconstruction options include that the plate can be removed should further excision be required, greater potential for long-term integration with surrounding tissues and the ability to be soaked in antibiotic to reduce the risk of infection.